Friction and Wear Reduction Mechanism of Polyalkylene Glycol-Based Engine Oils. Issue 4 (4th July 2018) - Gangopadhyay, A.; Liu, Z.; Simko, S. J.; Peczonczyk, S. L.; Cuthbert, J. B.; Hock, E. D.; Erdemir, A.; Ramirez, G.
ABSTRACT: Polyalkylene glycols (PAG) have been explored as a possible base stock for engine oil formulation. The friction, wear, and load-carrying capacity of five different PAG chemistries were evaluated either as a base stock or as formulated oils in pure sliding and sliding-rolling conditions using various laboratory bench test rigs operating under boundary and mixed lubrication regimes. The results were compared against GF-5 SAE 5W-20 and a mineral-based oil. The wear surfaces were also characterized using various surface-sensitive techniques for analysis of tribofilms to understand the mechanism of friction reduction. The results indicated that PAG oils show lower friction/traction coefficients and improved load-carrying capability, depending on the formulation, than those of the GF-5 SAE 5W-20 and mineral-based oil. The adsorption of PAG molecules on the surface appeared to be responsible for the lower friction characteristics.